Proses Komunikasi Simbolik Adat Mas Kawin Di Kampung Wayori Distrik Supiori Barat Kabupaten Supiori - Hepi Hastuti; Rani Maswati (Universitas Negeri Makassar, 2021)
Humans as social beings cannot live alone, humans are social creatures who in their daily life always need communication or interaction, since humans have lived in the world for centuries, they must have communicated symbolically, until the time when humans have entered the digital era. which in this era is marked by communication through advanced technology, so that the interaction symbols are increasingly diverse and are applied in the form of emoticons. Verbal communication is communication that uses oral and written, communication that uses words in both oral and written form. Talking face to face, talking using a cellphone is verbal communication while non-verbal is communication through automatic body movements and gestures. Communication that takes place in a reciprocal face-to-face dialogue interpersonal order is called symbolic interaction, interaction is a sociological term while symbolic is a communication term or communication science. The interaction process that is formed involves the use of language symbols, provisions of customs, religion and other views. This research method is descriptive qualitative where interviews are conducted on selected informants because they are considered credible in terms of the information we can get. The research location is in Wayori Village, Supiori Barat District, Supiori Regency. The results of this study indicate that the Supiori community is the dominant community in using oral communication, they are very very good at telling stories, but have a bit of difficulty in using writing as a communication product, so it is difficult to find stories. - stories in written form as historical relics.